KONSTRUKSI MEDIA ONLINE TENTANG PEMBERITAAN PERIZINAN MEIKARTA DI www.beritasatu.com DAN www.kompas.com EDISI SEPTEMBER 2017 - Roni Yusman (MediaKom : Jurnal Ilmiah Komunikasi, 2018)
Meikarta is the name of a city "New Jakarta" in Cikarang area of international scale. Amid the project development conducted by Lippo group there are licensing issues such as permission of Environmental Impact Assessment and Building Construction Permit. Mass media has a very important role for people’s lives. The content of the mass media is the consumption of information for the audience, so the mass media will affect the subjective reality of the perpetrators of social interaction. This study aims to examine the news conducted by online media beritasatu.com and kompas.com in presenting and delivering a news event Meikarta and explain the comparison of reality construction conducted by beritasatu.com and kompas.com. This research uses constructivist paradigm with qualitative approach. The analysis in this research uses analysis of Pan and Kosicky model. The results showed that framing beritasatu.com to permit Meikarta, tend to side with Meikarta and blame deputy Governor of West Java. The media ownership element affects this reporting. While kompas.com support the development of Meikarta and kompas.com is very careful in conveying facts and kompas.com trying to invite readers to see the real reality that private developers should not be inhibited its permission to do regional development.Keywords: Meikarta, Framing Pan dan Kosicky, Mass Media